MYOCARDIODYSTROPHY IN CHILDREN FROM THE POINT OF VIEW OF PATHOANATOMIST - B. I. Glukhovets ("Paediatrician" Publishers LLC, 2011)
The article discusses questions of etiology, pathogenesis and morphological signs of myocardiodystrophy in different periods of childhood. Functional disorders of cardiogenesis and hypoxic cardiopathy could be main causes of a disease. Author mark the necessity of systemic pathomorphological study of a heart with total analysis of contractile, conductive, microcirculation and neurovegetative structures in observation of cardiovascular pathology.